(untitled) (Modern education and development, 2024)
After the independence of the Republic of Uzbekistan, the attention to the social sphere, including the social sphere, increased. Social work is an activity aimed at solving social problems, supporting the population and improving their quality of life. This area is an integral part of the state policy, and it is implemented in order to provide social assistance to all layers of society, their social protection and increase their standard of living.